Risk, environment and modernity : towards a new ecology - Lash, Scott; Szerszynski, Bronislaw; Wynne, Brian (Theory, culture & society (Unnumbered), 1996)
This wide-ranging and accessible contribution to the study of risk, ecology and environment helps us to understand the politics of ecology and the place of social theory in making sense of environmental issues. The book provides insights into the complex dynamics of change in 'risk societies'.